A touch of sky : language and literature for the late adolescent - Ungson, Lourdes C. (Manila : Philippine Book Co, 1976)
A head of t.p. : Communication arts in English for the fourth year high school.
Includes bibliography.
Keywords: English language -- Study and teaching (Secondary); English language -- Rhetoric -- Study and teaching